2021
DOI: 10.1038/s41598-020-80539-z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and rheological properties of magnetic elastomers containing different shapes of corroded carbonyl iron particles

Abstract: Carbonyl iron particles (CIPs) is one of the key components in magnetic rubber, known as magnetorheological elastomer (MRE). Apart from the influence of their sizes and concentrations, the role of the particle’ shape is pronounced worthy of the attention for the MRE performance. However, the usage of CIPs in MRE during long-term applications may lead to corrosion effects on the embedded CIPs, which significantly affects the performance of devices or systems utilizing MRE. Hence, the distinctions between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Moreover, grease is classified as an intermediate state between fluid and solid, providing a certain freedom of movement to the magnetic particles to form columnar chains under the influence of a magnetic field [ 6 ]. Consequently, a higher MR effect of 952.38% was recorded for MRG compared to the 71.7% of solid-like-state MRE [ 7 , 8 ]. Additionally, compared with MRF, MRG does not require additional sealing to prevent any leakages of the devices as MRG has a self-sealing property due to its thick viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, grease is classified as an intermediate state between fluid and solid, providing a certain freedom of movement to the magnetic particles to form columnar chains under the influence of a magnetic field [ 6 ]. Consequently, a higher MR effect of 952.38% was recorded for MRG compared to the 71.7% of solid-like-state MRE [ 7 , 8 ]. Additionally, compared with MRF, MRG does not require additional sealing to prevent any leakages of the devices as MRG has a self-sealing property due to its thick viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…The model group results are obtained by calculation and fitting with ANSYS software during the calculation and analysis process, if the model conditions do not meet the set requirements, the calculation and fitting process will not be able to produce the research and analysis results. 35 This study successfully simulated the biomechanical stress and displacement results of the meniscus under different loading conditions. By comparison, it is found that the magnetorheological elastomer material has good mechanical properties, which can provide a reliable basis for clinical meniscus replacement surgery 36 (Figure 9).…”
Section: ■ Discussionmentioning
confidence: 99%
“…In order to understand various mechanical and rheological properties of both hard and soft magnetic materials, experimental characterisations are essential. Hence, over the years, an extensive amount of experimental studies have been conducted [28][29][30][31][32]. These experiments include tensile and compression tests under a wide range of deformation modes such as uniaxial, bi-axial (both equal and unequal), pure shear etc.…”
Section: Introductionmentioning
confidence: 99%